Current Experiences with Internet Telepathology and Possible Evolution in the Next Generation of Internet Services - V. Della Mea; C. A. Beltrami (Analytical Cellular Pathology)
The last five years experience has definitely demonstrated the possible applications of the Internet for telepathology. They may be listed as follows: (a) teleconsultation via multimedia e‐mail; (b) teleconsultation via web‐based tools; (c) distant education by means of World Wide Web; (d) virtual microscope management through Web and Java interfaces; (e) real‐time consultations through Internet‐based videoconferencing. Such applications have led to the recognition of some important limits of the Internet, when dealing with telemedicine: (i) no guarantees on the quality of service (QoS); (ii) inadequate security and privacy; (iii) for some countries, low bandwidth and thus low responsiveness for real‐time applications. Currently, there are several innovations in the world of the Internet. Different initiatives have been aimed at an amelioration of the Internet protocols, in order to have quality of service, multimedia support, security and other advanced services, together with greater bandwidth.